Coinage of the term ‘Political Islam’: Perspectives, Implications and prospects - Dr. Sajid Iqbal Sheikh; Dr. Muhammad Samiullah (jihat-ul-islam, 2021)
This paper aims to unfold genealogical notions backing the coinage of political Islam and its related discourses and attempts to search out its complementation or contradiction in contemporary political arena. Primarily, the study focuses on holistic and theoretical view of political Islam with its perspectives, implications and prospects. The study also aims to analyze the basic theory and current strategies of Islamic movements which may be considered the vanguard of Islamic revolution. These movements have created a certain discourse of political activism that is one of the matters of hottest debate in the contemporary world. Discourse analysis method with its approach of Critical Discourse Analysis (CDA) is going to be used and qualitative data collected from specific and relevant strata will be analyzed. The study argues that conspiracy theory is one of the key factors involved in offending political Islam and apparently, a valued segment of scholars concerned to the subject believe that Islamic political Theory must not be perceived as the source of violence and a root for terrorism discourses.